MEXICAN PIERIDAE WITH A DESCRIPTION OF NEW FORMS - VAZQUEZ, G LEONILA (Instituto Politécnico Nacional, Escuela Nacional de Ciencias Biológicas, CD MEXICO, DF, MEX, 1964)
A taxonomic study of butterflies from the Escalante and the Institute of Biology collections with descr of some new local forms
ANS INST BIOL
Keywords: MEXICAN, PIERIDAE, DESCRIPTION, FORMS; CIENCIAS DE LA VIDA; ETOLOGIA; INSECTOS